Analisis Kinerja Keuangan Bank Umum Syariah Sebelum dan Sesudah Pengalihan Dana Haji pada Bank Syariah - Lisa Erliana Marwan; Iwan Setiawan; Ine Mayasari (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Government policy through UU No 34 Thn 2014 about Hajj Fund Management said that the Hajj Fund Management should with the principle of sharia. Then in 2014, there was a transfer Hajj Fund from Conventional banks to Islamic banks. Hajj Fund that transferred to Islamic banks have a large value so it can give positive contribution to the financial performance such as DPK.The aim of this study was to find out the financial performance of 6 BPS BPIH before and after the transfer of Hajj Fund from conventional banks to Islamic banks. Taking case studies at PT. Bank Syariah Mandiri, PT. Bank BRI Syariah, PT. Bank BNI Syariah, PT. Bank Mega Syariah, PT. Bank Panin Dubai Syariah, and PT. Bank Muamalat. The Data that used in this study is Return On Assets (ROA) and Financing to Deposit Ratio (FDR) in Quarterly Financial Report of 6 BPS BPIH,4 years before the transfer of hajj fund that started 2010 until 2013, and 4 years after the transfer of hajj fund that started from 2015 until 2018. The method of data analysis in this study uses a different samples in non parametrik, which is Wilcoxon Signed Rank Test. The result of this study shows us that there was a difference in ROA and FDR of BPS BPIH before and after the transfer of hajj fund from conventional banks to Islamic banks.